Rlim/Rnf12, Rex1, and X Chromosome Inactivation - Wang, Feng; Bach, Ingolf (Frontiers in Cell and Developmental Biology, 2019)
RLIM/Rnf12 is an E3 ubiquitin ligase that has originally been identified as a transcriptional cofactor associated with LIM domain transcription factors. Indeed, this protein modulates transcriptional activities and multiprotein complexes recruited of several classes of transcription factors thereby enhancing or repressing transcription. Around 10 years ago, RLIM/Rnf12 has been identified as a major regulator for the process of X chromosome inactivation (XCI), the transcriptional silencing of one of the two X chromosomes in female mice and ESCs. However, the precise roles of Rlim during XCI have been controversial. Here, we focus on cellular and developmental functions of Rlim as an E3 ubiquitin ligase and its roles during XCI in conjunction with its target protein Rex1.